Molecular Detection and Genotyping of Male-Specific Coliphages by Reverse Transcription-PCR and Reverse Line Blot Hybridization - Vinjé, Jan (American Society for Microbiology, 2004)
In recent years, there has been increased interest in the use of male-specific or F+ coliphages as indicators of microbial inputs to source waters. Sero- or genotyping of these coliphages can also be used for microbial source tracking (MST). Among the male-specific coliphages, the F+ RNA (FRNA) viruses are well studied, while little is known about the F+ DNA (FDNA) viruses. We have developed a reverse line blot hybridization (RLB) assay which allows for the simultaneous detection and genotyping of both FRNA as well as FDNA coliphages. These assays included a novel generic duplex reverse transcription-PCR (RT-PCR) assay for FRNA viruses as well as a generic PCR for FDNA viruses. The RT-PCR assays were validated by using 190 field and prototype strains. Subsequent DNA sequencing and phylogenetic analyses of RT-PCR products revealed the classification of six different FRNA clusters, including the well-established subgroups I through IV, and three different FDNA clusters, including one (CH) not previously described. Within the leviviruses, a potentially new subgroup (called JS) including strains having more than 40% nucleotide sequence diversity with the known levivirus subgroups (MS2 and GA) was identified. We designed subgroup-specific oligonucleotides that were able to genotype all nine (six FRNA, three FDNA) different clusters. Application of the method to a panel of 351 enriched phage samples from animal feces and wastewater, including known prototype strains (MS2, GA, Qβ, M11, FI, and SP for FRNA and M13, f1, and fd for FDNA), resulted in successful genotyping of 348 (99%) of the samples. In summary, we developed a novel method for standardized genotyping of F+ coliphages as a useful tool for large-scale MST studies.